Pengaturan Batas Usia Perkawinan : Studi Komparatif Undang-Undang Perkawinan Negara-Negara Muslim (Indonesia dan Maladewa) - afrinald rizhan, afrinald rizhan (Syakhsia Jurnal Hukum Perdata Islam, 2024)
Abstract The regulation of the age limit for marriage in a country is an important factor inining the survival of marriage. The aim of this study is to find a comparison of marriage age limits in Indonesia and the Maldives. In this study the author uses a normative and comparative approach. The age limit in getting married is very important. Because marriage requires psychological maturity. The Quran and the Hadith do not specifically mention the minimum age for marriage. The commonly known requirement is to be well-informed, well-conscious, able to distinguish between good and bad so that it can give consent to marriage, until the time of a person to marry (buluq an-nishah), with the word "rusyd" In Indonesia, the amendment to the Act No. 1 of 1974 on Marriage, became the Law No. 16 of 2019, which sets the minimum marriage age for women equal to the minimum age of marriage for men, which is 19 (nine) years. In Maldives, the Maldivian State, the minimum age for marriage is 18 years with exceptions. However, according to Islamic law, individuals who have reached puberty can marry before the age of 18 with parental permission and registered in the Register of Marriages. Keywords: family law, marriage age, Indonesia, Maldives